(untitled) (Revista de Investigaciones Universidad del Quindío, 2022)
This study was carried out to determine the knowledge levels and sportive performances of the athletes playing tennis in the Eastern Anatolia Region. The research group consists of 167 volunteer athletes in licensed national/international tournaments in the Eastern Anatolia Region, Malatya. “Personal Information Form” and “Athlete Warm-up Habit” scale form, which determines the warming habits of athletes, were used as data collection tools. The data were analyzed using the SPSS statistical package program. The significance level was accepted as p<0.05. Of the athletes in the study, 54.5% had muscle-joint injuries, 79% did warm-up exercises, 58.1% did warm-up exercises between 11-20 minutes, and 42.5% had continuous warm-up exercises. It was determined that they did cool-down exercises, and 41.9% of them did cool-down exercises between 11-20 minutes. 91% of the research group stated that warm-up exercises reduce the risk of athlete injury, and 85% stated that warm-up exercises positively affect the joint areas and improve the athlete’s range of motion. It was determined that the mean score of the knowledge level of warming habits of the research group was at a reasonable level of 73.80±10.52.